Genetic Differentiation Within and Between Species of the Drosophila willistoni Group - Ayala, Francisco J. (1974)
We describe allelic variation at 28 loci in six Caribbean populations of four sympatric species of Drosophila. Within any one species the allelic frequencies are very similar from population to population, although there is evidence of local as well as regional genetic differentiation. The genetic distance is greater between populations from different islands than between populations of the same island. When the allelic frequencies are compared between different species, a remarkable pattern appears. In any pair of species nearly half of the loci have essentially identical allelic frequencies, while nearly the other half of the loci have different alleles and in different frequencies. The loci with nearly identical allelic frequencies are different when different pairs of species are compared. The patterns of allelic variation within and between species are inconsistent with the hypothesis that the variation is adaptively neutral. Migration or mutation cannot explain the patterns of genetic variation, either. Balancing natural selection is the main process maintaining protein polymorphisms in natural populations.